TECHNIQUE AND TECHNOLOGY OF PRODUCTION OF TWO-LAYER ROLLED WIRE SPIRAL CONSTRUCTIONS 2+7 AND 3+9 WITH DIFFERENT STEPS OF DISCHARGING BY LAYS IN ONE TECHNOLOGICAL OPERATION - Ju. L. Hudolej (Литьë и металлургия)
The way of the production of steel wire cord of the two-layer spiral constructions with the different lay paces in one technological operation, developed at RUP ''BMZ”, is presented. The calculations of the steel wire cord technological characteristics, parameters of the cable machine adjustment in technological operation are given. Advantages of the new way of the steel wire cord production, the ways of attainment of economic efficiency and alternative ways of its application at production of other steel wire cord constructions are pointed out”.